English The Effectiveness of the Use of Warrants and Warrants in Collecting Tax Arrears to Increase Tax Revenues (Study at KPP Pratama Surabaya Sukomanunggal) - Ida, Zuraidah; Alhabsyi, Muhamad Zainal Abidin (Jurusan Akuntansi Fakultas Ekonomi Universitas Islam 45, 2020)
The purpose of this study was to determine the effectiveness and contribution of the use of warning letters and forced letters in collecting tax arrears at KPP Surabaya Sukomanunggal in the 2016-2018 period. This type of research is a qualitative research with a descriptive approach. The data in this study consisted of primary data and secondary data. Data collection techniques using interviews and documentation. In this study illustrates the collection of tax arrears with letters of warning and forced letters in increasing tax revenue at KPP Pratama Surabaya Sukomanunggal. The analytical method used in this research is descriptive analysis using ratio analysis of effectiveness and contribution using calculation formulas. The results of this study indicate that the level of effectiveness of warning letters is classified as ineffective because the percentage of Warning Letter produced is still far below 60% caused by the low awareness of mandatory and the inability of taxpayers to pay their tax debt. While the forced letter as a whole is not enough to say effective because the percentage produced shows a downward trend caused by the lack of number of tax officers, especially the Tax Bailiff who plays an important role in the notification or delivery of the Forced Letter and also awareness of taxpayers in paying their low tax debt and also contributions made from letters of reprimand and forced letters are still lacking in tax revenues.